2018
DOI: 10.1080/10245332.2017.1413789
|View full text |Cite
|
Sign up to set email alerts
|

Is there a difference in phenotype between males and females with non-transfusion-dependent thalassemia? A cross-sectional evaluation

Abstract: This data should be considered in studies with experimental treatments aiming to correct anemia in patients with non-transfusion-dependent thalassemia. It should probably also be taken into account in order to set up different transfusion regimens among genders in transfusion-dependent patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Firstly, the prevalence of anemia was higher in females than males (5.53% vs 0.51%), which is similar to a study by Marsella M et al that adopted a cross-sectional evaluation. [ 26 ] Anemia is caused in most females through the loss of iron during pregnancy and menstruation. Secondly, the proportions of individuals with work-related pressure and social tensions were both higher among females than males (15.39% vs 13.61%, 8.22% vs 7.88%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the prevalence of anemia was higher in females than males (5.53% vs 0.51%), which is similar to a study by Marsella M et al that adopted a cross-sectional evaluation. [ 26 ] Anemia is caused in most females through the loss of iron during pregnancy and menstruation. Secondly, the proportions of individuals with work-related pressure and social tensions were both higher among females than males (15.39% vs 13.61%, 8.22% vs 7.88%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with TI usually do not need regular or frequent blood transfusion; thus, TI is a type of non-transfusion dependent thalassemia (NTDT) [23]. However, TI is not free of complications related to iron accumulation, in which hemostasis and hepcidin regulation are affected [45]. Iron is absorbed at higher rates through the intestinal mucosa in TI, promoting iron loading in different body tissues; if not treated with chelating therapies, iron toxicity develops, leading to the failure of various vital organs and finally death [56].…”
Section: Introductionmentioning
confidence: 99%
“…However, TI is not free of complications related to iron accumulation, in which hemostasis and hepcidin regulation are affected [45]. Iron is absorbed at higher rates through the intestinal mucosa in TI, promoting iron loading in different body tissues; if not treated with chelating therapies, iron toxicity develops, leading to the failure of various vital organs and finally death [56]. To measure iron overload, serum ferritin (SF) is commonly used as it is usually elevated during iron accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…36 Epidemiological studies suggested that there are no major differences in the prevalence of common complications among male and female thalassemia patients. 47 Nevertheless, male patients exhibit more cardiac morbidity and reduced survival, 48 and are more prone to bone disease. 49 Thus, male Th3/+ mice offer a physiologically relevant model to explore the roles of lipidome and intestinal microbiome in the development of iron overload-related cardiomyopathy in thalassemia.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic phenotype of male Th3/+ mice may be related to iron‐induced impaired insulin biosynthesis and secretion from pancreatic beta cells 46 but also to insulin resistance, which are common in thalassemia 36 . Epidemiological studies suggested that there are no major differences in the prevalence of common complications among male and female thalassemia patients 47 . Nevertheless, male patients exhibit more cardiac morbidity and reduced survival, 48 and are more prone to bone disease 49 .…”
Section: Discussionmentioning
confidence: 99%